Diskursus Etika Sosial bagi Kalangan Injili: Mengenal Pemikiran Reinhold Niebuhr melalui The Serenity Prayer - Wibowo, Romeo (Veritas : Jurnal Teologi dan Pelayanan, 2021)
Social Ethics Discourse for Evangelicals: Getting to Know Reinhold Niebuhr's Thoughts through the Serenity Prayer. Social ethics is not a major topic that is often discussed among evangelical Christians. Therefore, arise assumption that evangelical Christians tend to be pessimistic about situations globally and avoid issues in social ethics. This article offers a discourse on social ethics for evangelical Christians by introducing Reinhold Niebuhr’s thoughts. The serenity prayer is used as a method to frame Niebuhr’s thoughts. In Niebuhr’s view, man has a paradoxical reality. He is a sinful man who has limitations in exercising the pure love that Jesus taught. On the other hand, he is an image of God who can self-transcendence and think creatively to create newness in his life. Responding to this paradoxical reality, Niebuhr gave suggestions to build a realistic (dialectical) social ethics foundation that does not fall into an attitude of excessive optimism, let alone fall into an attitude of pessimism that tends to be fatalistic.